Pengaruh Arus Kas Operasi, Total Asset Turnover Dan Long Term Debt To Equity Ratio Terhadap Financial Distress Pada Perusahaan Subsektor Tekstil Yang Terdaftar Di Bursa Efek Indonesia (BEI) Tahun 2018-2020 - Fitri Fitri; Maria Hendriani; Zaenimar Windiani (Eqien - Jurnal Ekonomi dan Bisnis, 2023)
The Covid-19 virus outbreak has spread to almost all countries and started to enter Indonesia in 2020, having a negative impact on the country's economic situation. This situation has a broad impact on the process of production, distribution and other business activities, which can disrupt the country's economic performance. This study aims to examine the effect of operating cash flow, total asset turnover and long term debt to equity ratio on financial distress in textile sub-sector companies for the 2018-2020 period. The research method used is descriptive analysis. With the results of the research partially Operating Cash Flow does not significantly affect Financial Distress, Total Asset Turnover significantly affects Financial Distress, Long Term Debt to Equity significantly affects Financial Distress. Simultaneously the variables Operating Cash Flow, Total Asset Turnover, and Long Term Debt to Equity together have an effect on Financial Distress.